A-STREPTOCOCCAL INFECTION ON THE BORDER OF AGES - B. S. Belov (Научно-практическая ревматология, 2002)
At present group A streptococcal infection remains one of the important problems of medicine. From the middle of the 1980-cs number of diseases with group A streptococcal etiology significantly increased in many countries of the world. It coincided with return of disappeared from circulation highly toxigcnic and virulent serotypes M-l, M-3, M-5, M-18. Oulbreaks of acute rheumatic fever were registered among civil and military persons in USA. Wide distribution of tonsillitis, pharingitis and streptoderma in USA and in countries of Western Europe is accompanied by increase of invasive group A streptococcal diseases (bacteriemia, sepsis, necrotizing fasciitis and myositis, toxic shock syndrome) affecting predominantly working age people with fulminant development and high mortality reaching 80%. Causes of group A streptococcal infection epidemiology changes are not quite clear. Decrease of macroorganism immune response to above mentioned serotypes may play a role because their distribution was low for several decades. Created during evolution ability of some group of A streptococcal strains lo develop structural changes increasing virulence may also be one ol the causes. Main groups of antibiotics using for treatment of group A streptococcal infection are penicillines, cephalosporines, macrolides and lincosamides. Now practically in all countries of the world (including Russia) high frequency of group A streptococcal strains resistant to tetracyclines, co-trimonasol, sulphanilamides and chloramphenicol is noted in patients with angina and pharingitis. So these drugs should not be used in this form of infcclion. Efficacy of penicillines in invasive forms of group A streptococcal infection is low because of insufficient expression of penicillin-binding proteins by the microbe. Clindamycine is more effective in such cases.